Bridged bis(β-cyclodextrin)s-based polysaccharide nanoparticles for controlled paclitaxel delivery. Issue 34 (18th March 2016) - Chen, Li-Xia; Zhang, Ying-Ming; Cao, Yu; Zhang, Heng-Yi; Liu, Yu
Abstract : A dual-stimulus responsive polysaccharide nanoparticle was successfully constructed, in which the release of water insoluble paclitaxel could be readily achieved by the disulfide bond cleavage and the enzymatic degradation. Abstract : The lack of effective and specific carriers is generally considered as the main obstacle hindering further clinical applications in cancer therapy. In this work, a novel polysaccharide nanocarrier was successfully constructed by the noncovalent complexation of disulfide-containing bridged bis(β-cyclodextrin)s with adamantane-grafted hyaluronic acid. Possessing a three-dimensional hydrophobic microenvironment, the obtained binary nanoparticles could serve as a biocompatible platform for the loading and solubilizing of paclitaxel. More interestingly, spectroscopic and microscopic experiments revealed that the hydrophobic drug could be completely released from the nanocarrier through disulfide bond cleavage and enzymatic degradation. In addition, the active hyaluronic acid units endowed the resultant nanoparticles with desirable cell-specific targeting ability, thus leading to a relatively better anticancer activity toward tumor cells than free paclitaxel. We envision that the present work will provide a new method in the fabrication of more advanced macrocycle-based drug carriers.